Analisis Manajemen Risiko Menggunakan Framework 31000 dan Matriks Manajemen Risiko Pada Industri Pariwisata Religi Studi Kasus Travel Cahaya Insan Tafakkur - Lailafitri Pratiwi Kadmadi; Amelia Rahmadani; Indy Fauziah Hanifa; Putri Dewi Renggani; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The religious tourism industry is highly dynamic and complex, requiring systematic risk management to maintain service sustainability and pilgrim satisfaction. This study analyzes risk management at the religious tourism operator Travel Cahaya Insan Tafakkur by applying the ISO 31000:2018 framework and risk matrix to assess the likelihood and impact of risks. Using a qualitative approach through interviews and document reviews, this study identifies key risks including operational, service, security, and external risks. The assessment results show that some risks are in the moderate to high category, especially those related to travel schedule uncertainty, service quality, and pilgrims' health conditions. The implementation of ISO 31000 has proven to strengthen the structured process of risk identification, evaluation, and control. This study emphasizes the importance of risk management based on international standards to improve the reliability and sustainability of religious tourism services.